Effect of stationary factors on the yield and chemical composition of essential oils of Tetraclinis articulata (Vahl) Masters from Sdama Chergui massif’s (Tiaret, North-West Algeria) - Bensaadi, Nawel; Mhamed, Maatoug; Maatoug, Zakaria Zineddine; Kamel, Kamel (Journal of Agriculture and Applied Biology, 2024)
This paper aims to study the influence of exposure, altitude, and soil pH on the yield and chemical composition of essential oils (EOs) from the leaves of Tetraclinis articulata (Vahl) Masters, developed in the Sdama Chergui massif in northwestern Algeria. These EOs were obtained by hydrodistillation, resulting in average yields of 0.33±0.13 %, 0.29±0.07 %, 0.24±0.07 %, and 0.2±0.03 %, recorded at the south, west, north, and east exposures, respectively. Upon analyzing the obtained EOs by gas chromatography coupled with mass spectrometry (GC/MS), a total of chemical molecules grouped into 22 families were identified. The predominant compounds were Bornyl acetate (9.14 %, 7.95 %, 11.20 %, and 9.78 %), Limonene (5.03 %, 7.18 %, 5.76 %, and 5.41 %), α-Pinene (4.97 %, 5.26 %, 5.09 %, and 4.79 %), Camphor (7.53 %, 3.69 %, 3.01 %, and 5.91 %), and Borneol (5.20 %, 6.26 %, 4.93 %, and 5.11 %). Additionally, the analysis of these molecules by Factorial Analysis of Mixed Data (PCAmix) revealed that exposure, altitude, and soil pH have little effect on the yield and chemical composition of the essential oils of Tetraclinis articulata. Finally, careful attention to stationary parameters is crucial for obtaining essential oils of high quality and optimal quantity.